Milk yield of Cameroon Dwarf Blackbelly sheep - Njwe, R.M.; Manjeli, Y. (1992)
Analyses milk yield of Cameroon Dwarf Blackbelly sheep as was estimated by the indirect method of weighing lambs before and after suckling during a period of 12 weeks. Twenty-two lactations were evaluated between February and December 1985. Average daily milk yield ranged from 0.31 to 0.50 kg for ewes suckling single lambs. Maximum weekly milk yield (3.52 kg) was attained during the 4th week of lactation after which production declined. Differences in milk yield between ewes and weeks of lactation were highly significant.